The Influence of Social Marketing Campaign on Community Decisions to Pay Zakat at BAZNAS Through the Kitabisa.com Fintech Platform - Tahiyati, Azka; Tartila, Muzayyana (Institut Agama Islam (IAI) SEBI, 2023)
This study aims to: (1) test the effect of creating awareness and attraction (X1), changing attitudes and conditions (X2), motivating people to change behavior (X3), empowering people to act (X4) to pay zakat decisions (Y). This study uses an explanatory method. Data was obtained by distributing questionnaires online to 101 respondents who had paid zakat on BAZNAS through the fintech platform Kitabisa.com. The sampling technique used in this study was purposive sampling. The research method used is quantitative associative research and the data analysis tool used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results of this study indicate that creating awareness and attraction (X1) and empowering people to act (X4) significantly influence the decision to pay zakat (Y), while changing attitudes and conditions (X2) and motivating people to change behavior (X3) has no significant effect on decision to pay zakat (Y). Based on the test of the coefficient of determination obtained the value of R square 59.2% and the remaining 40.8% is influenced by other exogenous variables outside the model studied. So, for the next researcher is expected to conduct research by using exogenous variables outside the research conducted by the researcher.